THE ROLE OF CULTURE ON THE TRANSLATION OF METAPHOR - Makhmudova Gulbakhor Bakhrom kizi (Journal of new century innovations, 2023)
Abstract: This article investigates the notion of “culture”, the correlations between culture and metaphor. Moreover, the influence of culture in metaphor translation process and how this impact can create the barriers in translation science. The purpose of this paper is to demonstrate an analytical view into the ability of translating of metaphoric expressions and how it is considered to be vitally important in the process of meaning-making.